TRAFFIC CONGESTION LEVEL IN 10 SELECTED CITIES OF POLAND - Jacek CABAN (Scientific Journal of Silesian University of Technology. Series Transport, 2021)
Transport has a great impact on human activities but contributes to many negative phenomena occurring in road traffic, for example, road traffic accidents, emission of toxic exhaust fumes into the atmosphere and a high share of cars in road traffic. For the above reasons, many initiatives have been taken in the field of road traffic management and urban logistics. Based on a literature review, it was found that the problem of the phenomenon of traffic congestion in urban areas remains an ongoing issue. In the first part of this article, the theoretical issues of traffic flow and congestion formation in the city road networks were presented. While the second part outlines the situation of transport congestion in 10 Polish cities based on the worldwide TomTom Traffic Index in the years 2008-2018. This study is a brief analysis of the trends relating to transport congestion based on the TomTom Traffic Index in these cities.